TEACHING READING COMPREHENSION IN RECOUNT TEXT BY USING ZOOMING IN AND ZOOMING OUT (ZIZO) STRATEGY TO THE EIGHTH GRADE STUDENTS OF SMP SRIGUNA PALEMBANG - Ekha yasthi (Edukasi, 2016)
There are two purposes of this study. First, to find out whether or not there is a significant difference on the eighth grade students’ recount reading between those who are taught by using Zooming In and Zooming Out (ZIZO) strategy and those who are not at SMP Sriguna Palembang. Second, to find out whether or not there is a significant improvement on the eighth grade students’ recount reading before and after the treatment. This study used quasi-experimental design that is pretest-posttest non-equivalent group design. The population of the study was all of the eighth grade students of SMP Sriguna Palembang. The sample of the study was selected by using convenience sampling method. The samples of this study were class VIII.6 as control class and VIII.7 as experimental class. Both of classes consist of 70 students. This study used independent sample t-test and paired sample t-test. To verify the hypotheses, the score data between posttest in experimental and control groups were analyzed by using independent sample t-test. In independent t-test, level of significance is (0.001), df (68), t-value (3.390) and t-table (2.000). Then, the score data between pretest and posttest in experimental groups were analyzed by using paired sample t-test. In paired t-test, level of significance is (0.000), df (34), t-value (9.171) and t-table (2.042). It means that there was a significant difference on the eighth grade students’ recount reading who were taught by using ZIZO strategy and those who are not. Then, there was a significant improvement on the eighth grade students’ recount reading before and after the treatment since the p-output was lower than 0.05 and t-value was higher than t-table.